HUBUNGAN PROMO CASHBACK TERHADAP LOYALITAS PELANGGAN MUSLIM SURABAYA DALAM PELAYANAN DIGITAL WALLET OVO - Amelia, fitri; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2020)
The growth of Indonesia's digital economy since 2016 has grown rapidly, one of which is the presence of digital wallet. The best digital wallet in Indonesia is Ovo with the cashback promo service that makes customers feel given the convenience to transact. This research aims to exemine the relationship between cashback promotion with muslim customer's loyalty in digital wallet Ovo services. This study is using quantitative method with descriptive approach. The number of respondents with a total of 100 respondents Ovo users in Surabaya. The data collection technique of this research using questionnaire method then measured on a Likert scale and analysed with the help of SPSS Statistics version 23 software. The results of this study indicated a low relationship between cashback promotion with muslim customer's loyalty in digital wallet Ovo services.